Ultrahigh-resolution spectroscopy for methyl mercaptan at the ν2-band by a distributed feedback interband cascade laser. (July 2017) - Du, Zhenhui; Li, Jinyi; Gao, Hong; Luo, Gang; Cao, Xiuhan; Ma, Yiwen
Abstract: The ultrahigh-resolution mid-infrared absorption spectrum of methyl mercaptan (CH3 SH) was recorded and analyzed in the region of 2945–2953 cm -1, where the strong ν 2 -band is located. Benefitting from the high-resolution of tunable laser absorption spectrometry (TLAS) with a distributed feedback interband cascade laser (DFB-ICL), 12-strong and 27-weak air-broadened absorption peaks belonging to the ν2 -band of CH3 SH were assigned with resolution of better than 2.24×10 -5 cm -1 ( 26 fm/670 kHz) and absorption cross section precision of 2.0%, at temperature of 298.15 K and pressure of 1 atm. For further description of the assigned transitions, the spectral line parameters and cross sections of these absorption peaks versus pressure were investigated. These ultrahigh resolution air-broadened spectra can be used as reference data for CH3 SH remote sensing and absolute spectral measurement applications. Highlights: Ultrahigh-resolution absorption spectroscopy of the ν2 band of methyl mercaptan at room temperature. Air-broadened line positions, intensities and for 39 transitions. Validation of spectroscopic data. Comparison to the PNNL is discussed.